MiR‐1246 is implicated as a possible candidate for endometrium remodelling facilitating implantation in buffalo (Bubalus bubalis). Issue 1 (25th October 2022) - Dubey, Pratiksha; Batra, Vipul; Sarwalia, Parul; Nayak, Samiksha; Baithalu, Rubina; Kumar, Rakesh; Datta, Tirtha Kumar
Abstract: Background: The microRNAs (miRs) secreted by the trophectoderm (TE) cells have recently been implicated in the conceptus‐endometrial cross talk during implantation and placentation. These miRs modulate various cellular processes during conception and throughout the pregnancy by regulating the gene expression in the foetal and maternal tissues. Objectives: This study was undertaken to elucidate the function of TE secreted miRNAs in the maternal‐foetal cross‐talk during implantation/placentation in buffalo. Methods: The in vitro produced blastocysts were cultured on a cumulus feeder layer for 21 days. The relative expression profiles of a selected panel of miRs was generated using the spent media collected on Days 0, 7, 12, 16, and 21. A custom‐designed mirVana™ miRNA mimic was used to transfect the endometrial epithelial cells (EECs) in order to determine the role of miRNA exhibiting highest expression on Days 21 and 21. Results: The expression of miR‐1246 ( p < 0.001) and let‐7b ( p < 0.01) was found to be significantly higher on Day 21 of TE culture in comparison to the control (Day 0). This elevated expression indicated the involvement of these miRs in the maternal‐foetal cross‐talk. Interestingly, after the transfection of EECs with miRNA mimic for miR‐1246 (a novel molecule vis‐à‐vis implantation), the expression of beta‐catenin and mucin1 in these cells was found to be significantly ( p < 0.05) downregulated vis‐à‐vis the control, that is, the IFN‐τ primed EECs (before transfection). Conclusions: The TE secreted miR‐1246 appeared to lower the expression of the endometrial receptivity genes (mucin1 and beta‐catenin) which apparently assists the endometrium in preparing for placentation. Abstract : This study was undertaken to elucidate the function of TE secreted miRNAs in the maternal‐fetal cross‐talk during implantation/placentation in buffalo. The transfection of TE secreted miR‐1246 in endometrial cells appeared to lower the expression of the endometrial receptivity genes (mucin1 and beta‐catenin) which apparently assists the endometrium in preparing for placentation.